EMG analysis on gait rehabilitation : influence of walking speed and body weight support system. - Lee, Lynette Yan Li. (2009)
There is a growth in hospitals and rehabilitation centers using body-weight supported system for gait rehabilitation. Together with robotic device, it is believed to help in reducing the number of therapists needed and also achieve better gait improvement. Hence, this research is done hoping to obtain significant results that can contribute to effective gait rehabilitation. An EMG study was conducted to determine the main muscles responsible for gait. After which, the activation of the major muscles were investigated with different walking speed. In the third stage, subjects were required to walk with the body-weight support (BWS) system. The major muscles were then investigated with different walking speed and weight offload. From the first study, soleus, tibialis anterior, gastrocnemius, vastus lateralis, rectus femoris, bicep femoris, semitendinosus / semimembranous and gluteus maximus were chosen for subsequent investigations. It is found that the muscles generally have increased activation at higher walking speed. Muscle activation of soleus and gastrocnemius is found to be more sensitive to changing walking speed. When changing the weight offload for the BWS system, it is found that it affects the stance phase while the swing phase remains almost unchanged. Gastrocnemius is again the most sensitive to the change in weight offload. The findings suggest that gait training with increased walking speed or weight offload affects differently on each muscle and influence only certain phase of a gait cycle. Thus, it is important to be able to identify the abnormalities of each patient and design a customize gait training in order to effective improve their walking ability.